Knowledge and Attitude of MBBS Students Regarding Post Mortem Examination: A Cross-sectional Study in Chennai Region - Karthika J.; R. Monisha (Indian Journal of Forensic Medicine and Pathology, 2026)
Background: An autopsy is a systematic examination of a dead body for medical,legal, or scienti𿿿c purposes. A medicolegal autopsy is conducted to determine thecause, time, and manner of death, establish identity, and decide whether the death is natural or unnatural. In India, all unnatural deaths must undergo a medicolegal autopsy to ensure justice. For MBBS students, attending autopsy postings is essential for understanding real-life postmortem procedures and preparing them for future responsibilities as medical of𿿿cers. However, many students hesitate toattend autopsies due to fear, misconceptions, or lack of exposure. This study aimed to assess students’ knowledge, attitudes, and barriers related to medicolegal and clinical autopsies. Objectives: The primary objective was to evaluate medical students’ knowledgeand attitudes toward postmortem examination and their interest in forensic medicine as a career. Secondary objectives included identifying associations withdemographic factors (age, gender, prior exposure) and exploring misconceptions and barriers to attending autopsy postings. Methods: A cross-sectional questionnaire-based study was conducted among Phase II to Phase IV MBBS students and interns at Chettinad Hospital andResearchInstitute, Chennai. A structured and validated questionnaire was administeredto205 participants. It assessed demographic details, knowledge, attitudes, practices, and perceptions regarding postmortem examination. Data were analysed descriptively. Results: Most participants were Phase II students aged 19-20 years (mean age 19.6 years). Overall knowledge was satisfactory. About 87%knewthat police or Magistrate requisition and an inquest report are required before medicolegal autopsy. Around 85% understood its purpose, and 93%knewpartial autopsyis not allowed. Knowledge about organ preservation was limited (51.9%). Most students were aware of proper body storage (82.4%) and virtopsy (75.9%). Regarding attitude, 69.9% supported compulsory autopsy exposure. While 78.5%were willing to handle a dead body, 60.7% were hesitant to appearin court. Interest in forensic medicine as a career was expressed by 65.4%. Conclusion: Students showed good basic knowledge and a positive attitude, but practical skills and con𿿿dence, especially regarding court duties needs improvement through increased hands-on training and mock court sessions.